Some factors affecting the birth weight of the Butana and Kenana calves - Khalifa, H.A. (1966)
Butana and Kenana calves' performance were evaluated. Effects of type of breed, sex of calf, age of dam, sequence of calving and season of calving on calf birth weights were examined based on records of 256 Butana and 169 Kenana calves. Data from statistical analysis of variances and correlation between each parameter and birth weight are included.